RELEVANSI TAHNIK DAN AQIQAH SEBAGAI HAK ANAK DAN IMPLIKASINYA TERHADAP PENDIDIKAN ISLAM KONTEMPORER - Nabil Tito Prasetyo; Erliyana, Idham Kholid; Fachrul Gazi, Erlina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Tahnik and aqiqah are two sunnah practices in Islam performed at the birth of a child. This article exploresthe relevance of these two practices as part of children's rights in Islam and examines how theirimplementation can influence contemporary Islamic education. The research employed a library study method with textual analysis of the Qur'an, hadith, and current academic literature. The results found thattahnik and aqiqah have fundamental symbolic, spiritual, social, and educational functions as children's rights. Implications for contemporary Islamic education include the integration of practical values into the curriculum, the character of education from the neonatal period, and the role of parents and society insupporting child development.